Persepsi Masyarakat Kretek Kabupaten Bantul Terhadap UpayaPencegahan Demam Berdarah Dengue Selama Pandemi COVID-19. - SHEBILLA MEIKY PUTRI (Universitas Ahmad Dahlan, 2022)
Background: The COVID-19 pandemic that can hinder dengue prevention and control measures can cause a new disaster in dengue cases. Prevention and control of dengue can be influenced by public perceptions of dengue disease. Based on the background, the researcher is interested in analyzing the perception of the Kretek community in Bantul Regency towards efforts to prevent dengue hemorrhagic fever during the COVID-19 pandemic. Method: This research is a descriptive qualitative research. This study uses a case study design or case study. The informants interviewed consisted of key informants, namely 3 residents Bantul Regency who were declared dengue fever during the pandemic and had been decl